Is retrograde nailing superior to lateral locked plating for complete articular distal femur fractures?. Issue 2 (February 2022) - Chandra Vemulapalli, K.; Pechero, Guillermo R.; Warner, Stephen J.; Achor, Timothy S.; Gary, Joshua L.; Munz, John W.; Choo, Andrew M.; Prasarn, Mark L.; Chip Routt, Milton L.
Highlights: Decreased nonunion rate with retrograde nailing compared to lateral locked plating. Decreased coronal plane malalignment with retrograde nailing compared to lateral locked plating. Average time to union in both groups was 6 months and 6.6 months respectively. Abstract: Introduction: Nonunion rates for distal femur fractures treated with lateral locked plating (LLP) remains as high as 18–22% despite significant advances with implant design and construct modulation. However, whether treatment of distal femur fractures with rIMN has improved outcomes compared to LLP has not been well characterized. The purpose of this study was to compare outcomes of complete articular distal femur fractures (AO/OTA 33-C) treated with either LLP or rIMN. Methods: 106 distal femur fractures in 106 patients between January 2014 and January 2018 were identified. Medical records were reviewed to collect patient age, gender, body mass index, sagittal and coronal plane alignment on immediate postoperative radiographs, time to union, incidence of nonunion, and incidence of secondary operative procedures for repair of a nonunion. Results: Of 106 patients, 50 underwent rIMN and 56 underwent LLP. The mean age at the time of injury was 51 years (21 to 86 years) and there were 55 males. Average coronal alignment of 83.7° of anatomic lateral distal femoral angle (aLDFA) and sagittal alignment of <1° of apex anterior angulation in the rIMN group. In the LLP group there was an average of 87.9° of aLDFA and 1.9° of apex anterior angulation ( p = .005 and p = .36). Average time to union in the rIMN group was 6 months and 6.6 months in the LLP group ( p = .52). Incidence of nonunion in the rIMN group was 11.8% and 27.5% in the LLP group ( p = .008). There were 8 secondary procedures for nonunion in the rIMN group and 18 in the LLP group ( p = .43). Conclusions: Our results demonstrated a higher nonunion rate and coronal plane malalignment with LLP compared to rIMN. While prospective data is required, rIMN does appear to be an appropriate treatment for complete articular distal femur fractures with a potentially decreased rate of nonunion .